WRINKLED1 Regulates BIOTIN ATTACHMENT DOMAIN-CONTAINING Proteins that Inhibit Fatty Acid Synthesis . Issue 1 (17th June 2019) - Liu, Hui; Zhai, Zhiyang; Kuczynski, Kate; Keereetaweep, Jantana; Schwender, Jorg; Shanklin, John
Abstract : WRINKLED1 regulates genes for fatty acid synthesis as well as inhibitors of fatty acid synthesis (BADCs) in a homeostatic mechanism. Abstract: WRINKLED1 (WRI1) is a transcriptional activator that binds to a conserved sequence (designated as AW box) boxes in the promoters of many genes from central metabolism and fatty acid (FA) synthesis, resulting in their transcription. BIOTIN ATTACHMENT DOMAIN-CONTAINING (BADC) proteins lack a biotin-attachment domain and are therefore inactive, but in the presence of excess FA, BADC1 and BADC3 are primarily responsible for the observed long-term irreversible inhibition of ACETYL-COA CARBOXYLASE, and consequently FA synthesis. Here, we tested the interaction of WRI1 with BADC genes in Arabidopsis ( Arabidopsis thaliana ) and found purified WRI1 bound with high affinity to canonical AW boxes from the promoters of all three BADC genes. Consistent with this observation, both expression of BADC1, BADC2, and BADC3 genes and BADC1 protein levels were reduced in wri1-1 relative to the wild type, and elevated upon WRI1 overexpression. The double mutant badc1 badc2 phenocopied wri1-1 with respect to both reduction in root length and elevation of indole-3-acetic acid-Asp levels relative to the wild type. Overexpression of BADC1 in wri1-1 decreased indole-3-acetic acid-Asp content and partially rescued its short-root phenotype, demonstrating a role for BADCs in seedling establishment. That WRI1 positively regulates genes encoding both FA synthesis and BADC proteins (i.e. conditional inhibitors of FA synthesis), represents a coordinated mechanism to achieve lipid homeostasis in which plants couple the transcription of their FA synthetic capacity with their capacity to biochemically downregulate it.